Pembelajaran Berbasis Masalah untuk Belajar Bahasa Indonesia di SMA Muhammadiyah Ternate - Siti Mahnun (Kantor Bahasa Provinsi Maluku Utara, 2016)
During this learning Indonesian in class XII IPS SMA Muhammadiyah Ternate not apply constructivism learning and contextual learning. Therefore, they often found sev eral facts in learning activities: (1) the students speak for themselves, (2) some students confused capture the teacher's instructions, (3) some students did not dare ask, (4) a bit of an interaction between students, and (5 ) even students bored and tired of the Indonesian language teaching. This study aims to determine the effectiveness of learning Indonesian students in grade XII IPS SMA Muhammadiyah Ternate through the application of problem-based learning. This study used a qualitative approach. This research is a classroom action research. The results showed that the application of problem-based learning can improve learning outcomes of students of class XII IPS SMA Muhammadiyah Ternate exhibited by the students' ability to express an opinion in the form of criticism and essays.